Introduction: For Love Or Money? Defining Relationships in Law and Life - Marion Crain; Kimberly D. Krawiec (Washington University Journal of Law & Policy, 2011)
The article focuses on relationships in the light of law and life. It cites the book “Working Relationships,” by Laura Rosenbury wherein the author points on the importance of social ties at work particularly on the legal dichotomy between intimacy, and production. Ethan Leib affirmed the significance of employment where intimacy is formed. Moreover, Mary Anne Case, author of “Enforcing Bargains in an Ongoing Marriage,” says that courts are unwilling to enforce bargains in an ongoing marriage.
Keywords: Law & behavioral economics; Interpersonal relations; " Working Relationships" [book]; Laura Rosenbury; Social ties & work; Intimacy & production